2006
DOI: 10.1017/s1740925x07000385
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of neuregulin 1 expression by progesterone in astrocytes and neurons

Abstract: Glial2neuronal interactions are crucial processes in neuromodulation and synaptic plasticity. The neuregulin 1 family of growth and differentiation factors have been implicated as bidirectional signaling molecules that are involved in mediating some of these interactions. We have shown previously that neuregulin 1 expression is regulated by the gonadal hormones progesterone and 17b-estradiol in the CNS, which might represent a novel, indirect mechanism of the neuromodulatory actions of these gonadal hormones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
1
17
0
2
Order By: Relevance
“…Many experimental studies, most performed in rodents, have shown that progesterone has multiple action in the CNS and that it has considerable influence on the functioning of neurons and glial cells [57, 58]. Our findings support the premise that progesterone contributes to post-stroke functional recovery by decreasing VEGF and increasing BDNF and neurogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…Many experimental studies, most performed in rodents, have shown that progesterone has multiple action in the CNS and that it has considerable influence on the functioning of neurons and glial cells [57, 58]. Our findings support the premise that progesterone contributes to post-stroke functional recovery by decreasing VEGF and increasing BDNF and neurogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…Because microglia do not express mRNA for PR (Sierra et al,2008), the peroxidase labeling found here is believed to be present in astrocytes. PR mRNA and function have been described in astrocytes derived from rat forebrain (Jung‐Testas et al,1992) and cortex (Lacroix‐Fralish et al,2006). Astrocytes play a role in synaptic transmission, generate trophic factors, and direct the development and maturation of individual synapses (Villoslada and Genain,2004; Nishida and Okabe,2007; Perea and Araque,2007).…”
Section: Discussionmentioning
confidence: 99%
“…All drugs were prepared in sterile 0.1% bovine serum albumin (BSA)/PBS. CD14 doses were chosen based on our previous experience using intrathecal drug administration (Cauwels et al, 1999a, Lacroix-Fralish et al, 2006b) and pilot dose response experiments. The experimenter injecting the mice was blinded to the type of solution being used.…”
Section: Methodsmentioning
confidence: 99%